Development and validation of a subcritical 1, 1, 1, 2‐tetrafluoroethane extraction technique: Gas chromatography–mass spectrometry method for the simultaneous determination of polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and polybrominated biphenyl ethers in aquatic products. Issue 21 (17th October 2017) - Xu, Feiyue; Feng, Xiaomei; Shi, Nianrong; Pan, Jiangbo; Zhan, Huashu; Han, Yuqian
Abstract: A simple, rapid, and green method was developed for the simultaneous analysis of polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and polybrominated biphenyl ethers in aquatic products using subcritical 1, 1, 1, 2‐tetrafluoroethane extraction coupled with gas chromatography and mass spectrometry. Effects of the extraction temperature, pressure, and cosolvent volume on the extraction efficiency were investigated by extracting spiked oyster samples. The results show that the maximum extraction efficiency was obtained at 40°C, 12 MPa, and a cosolvent (dichloromethane) volume of 5.0 mL. Under these conditions, the calibration curves had good linearity with square of the correlation larger than 0.998 in the concentration range of 5–800 ng/mL; limit of detection and limit of quantitation were 0.16–2.83 and 0.55–9.43 ng/g, respectively. At spiked levels of 10, 30, and 50 ng/g, the average recoveries were 70.4–80.4% for polycyclic aromatic hydrocarbons, 74.0–83.6% for polychlorinated biphenyls, and 66.9–78.0% for polybrominated biphenyl ethers, with average relative standard deviations of less than 16.3%. The established method has no significant differences in recovery compared to traditional methods and is suitable for the analysis of real samples.